Chelate‐Thiolate‐Coordinate Ligands Modulating the Configuration and Electrochemical Property of Dinitrosyliron Complexes (DNICs). Issue 45 (25th September 2015) - Yeh, Shih‐Wey; Lin, Chih‐Wei; Liu, Bai‐Heng; Tsou, Chih‐Chin; Tsai, Ming‐Li; Liaw, Wen‐Feng
Abstract As opposed to the reversible redox reaction (Fe(NO)210 reduced‐form DNIC [(NO)2Fe(S(CH2)3S)]2− (1)⇌Fe(NO)29 oxidized‐form [(NO)2Fe(S(CH2)3S)]−), the chemical oxidation of the Fe(NO)210 DNIC [(NO)2Fe(S(CH2)2S)]2− (2) generates the dinuclear Fe(NO)29–Fe(NO)29 complex [(NO)2Fe(μ‐SC2H4S)2Fe(NO)2]2− (3) bridged by two terminal [SC2H4S]2− ligands. On the basis of the Fe K‐edge pre‐edge energy and S K‐edge XAS, the oxidation of complex 1 yielding [(NO)2Fe(S(CH2)3S)]− is predominantly a metal‐based oxidation. The smaller S1‐Fe1‐S2 bond angle of 94.1(1)° observed in complex 1 (S1‐Fe1‐S2 88.6(1)° in complex 2), compared to the bigger bond angle of 100.9(1)° in the Fe(NO)29 DNIC [(NO)2Fe(S(CH2)3S)]−, may be ascribed to the electron‐rich Fe(NO)210 DNIC preferring a restricted bite angle to alleviate the electronic donation of the chelating thiolate to the electron‐rich Fe(NO)210 core. The extended transition state and natural orbitals for chemical valence (ETS‐NOCV) analysis on the edt‐/pdt‐chelated Fe(NO)29 and Fe(NO)210 DNICs demonstrates how two key bonding interactions, that is, a FeS covalent σ bond and thiolate to the Fe d<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkwbw5t1s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> z 2</alternatives> charge donation, between the chelating thiolate ligand and the Fe(NO)29/10 core could be modulated by the backbone lengths of the chelating thiolate ligands to tune the electrochemical redox potential (E1/2=−1.64 V for complex 1 and E1/2=−1.33 V for complex 2) and to dictate structural rearrangement/chemical transformations (S‐Fe‐S bite angle and monomeric vs. dimeric DNICs).